Mantle genesis and crustal contamination in Carboniferous granitoids using U-Th-K concentrations at the Akşar Pluton in the Eastern Pontides, NE Türkiye - Maden, Nafız; Gücer, Mehmet Ali; Akaryalı, Enver (Journal of applied geophysics, 2025)
New radiogenic heat production (RHP) data are presented for Carboniferous granites outcropping in the Akşar region (Bayburt, NE Turkey) to contribute to ongoing debates on the genetic and lithologic relationship between the Akşar and Gümüşhane plutons, which is the most widely distributed granitic rocks in the region. The scope of this study consists of rocks composed of enriched mantle material metasomatized by fluids from the previously subducted plate. We observed average K value for the Akşar Pluton was found to be 3.09 ± 1.58 %. Additionally, average Th/U and U/Th values of 3.95 ± 1.37 and 0.29 ± 0.10, respectively. The calculated RHP value for the Akşar Pluton was 2.20 ± 0.56 μWm−3. Numerical results suggest that the Carboniferous Akşar pluton's primary magma was the product of mixing lithospheric mantle and mid-to-lower crustal melts because of partial melting, differentiation, and emplacement in the shallow continental magma chamber. The geochemical and petrogenetic characteristics of the Akşar region magmas suggest that crustal contamination occurred at multiple levels, particularly within the lower to middle crust of the plutonic core complex. This complex likely retains geochemical signatures indicative of subducted Paleotethys oceanic lithosphere. These findings provide critical insights into the magmatic evolution of the Eastern Pontides, contributing to a more comprehensive understanding of crust–mantle interactions and the broader geodynamic framework of northeastern Türkiye. •New RHP data for Akşar Pluton indicate mantle-crustal melt mixing.•High Th/U ratios suggest significant crustal contamination during magma ascent.•RHP values are primarily controlled by Th content, with minor K and U contributions.•Subduction signature evident in Carboniferous pluton geochemistry.•Density and radiogenic heat production data support upper crustal emplacement.